Annexin A2: the missing piece in the puzzle of pathogen-induced damage - Chao Li; Jianwei Yu; Daoyong Liao; Xiaoling Su; Xinchao Yi; Xue Yang; Jun He (Virulence, 2023)
ABSTRACTAnnexin A2 is a Ca2+ regulated protein belonging to the Annexin family and is found in the cytoplasm and cell membrane. It can exist in a monomeric form or in a heterotetrameric form with the S100A10 dimer. The research on Annexin A2 in tumours is currently active, and studies on its role in pathogen infection are increasing. Annexin A2 plays a crucial role in the life cycle of viruses by mediating adhesion, internalization, uncoating, transport, and release. In the case of parasites, bacteria, mycoplasma, fungi, and other pathogens, Annexin A2 binds to the ligand on the pathogen, which mediates the pathogen’s adhesion to the host cell, ultimately leading to infection and damage to the host. Furthermore, some studies have developed biological or chemical drugs that target Annexin A2, which have demonstrated promising anti-infective effects. Thus, targeting Annexin A2 may present a promising therapeutic approach for the treatment of diverse infectious diseases. In summary, this paper provides an overview of Annexin A2 and its role in various pathogens. It highlights its regulation of pathogen infection and its potential as a therapeutic target for the treatment of infectious diseases.